Acute and Chronic Pancreatitis Disease Prevalence, Classification, and Comorbidities: A Cohort Study of the UK BioBank. Issue 1 (19th January 2022) - Spagnolo, Daniel M.; Greer, Phil J.; Ohlsen, Celeste Shelton; Mance, Shannon; Ellison, Mitchell; Breze, Cameron; Busby, Ben; Whitcomb, David C.; Haupt, Mark
Abstract : INTRODUCTION: Pancreatitis is a complex syndrome that results from many etiologies. Large well-characterized cohorts are needed to further understand disease risk and prognosis. METHODS: A pancreatitis cohort of more than 4, 200 patients and 24, 000 controls were identified in the UK BioBank (UKBB) consortium. A descriptive analysis was completed, comparing patients with acute (AP) and chronic pancreatitis (CP). The Toxic-metabolic, Idiopathic, Genetic, Autoimmune, Recurrent, and severe pancreatitis and Obstructive checklist Version 2 classification was applied to patients with AP and CP and compared with the control population. RESULTS: CP prevalence in the UKBB is 163 per 100, 000. AP incidence increased from 21.4/100, 000 per year from 2001 to 2005 to 48.2/100, 000 per year between 2016 and 2020. Gallstones and smoking were confirmed as key risk factors for AP and CP, respectively. Both populations carry multiple risk factors and a high burden of comorbidities, including benign and malignant neoplastic disorders. DISCUSSION: The UKBB serves as a rich cohort to evaluate pancreatitis. Disease burden of AP and CP was high in this population. The association of common risk factors identified in other cohort studies was confirmed in this study. Further analysis is needed to link genomic risks and biomarkers with disease features in this population.